TQM implementation : a conceptual study of the impact of implementation on two companies : a comparative investigation about the understanding of and impact of Total Quality Management programmes within Post Haste Couriers, Palmerston North and Rayonier New Zealand, Wellington : a thesis presented in partial fulfilment of the requirements of the degree of Master of Business Studies at Massey University - Fowler, Richard John (Massey University, 1996)
Much has been written about the concepts associated with TQM, but little exists on the impact of TQM implementation in New Zealand companies. This paper is a comparative study on the understandings and impact of TQM within two New Zealand companies, Post Haste Couriers Palmerston North and Rayonier New Zealand, Wellington. Semi structured interviews were carried out and the data compared with a variety of theoretical approaches. The findings show that TQM means different things to different levels in a companies hierarchy and its successful implementation depends on the management style, company resourcing and the amount of control that can be exercised over the business environment.
Keywords: Total quality management; New Zealand